2009
DOI: 10.4088/jcp.08m04181
|View full text |Cite
|
Sign up to set email alerts
|

Mild Behavioral Impairment and Risk of Dementia

Abstract: Background Mild cognitive impairment (MCI) is a transitional state between normal ageing and dementia, at least for some patients. Behavioral symptoms in MCI are associated with a higher risk of dementia, but their association with dementia risk in patients without MCI is unknown. Mild Behavioral Impairment (MBI) refers to a late life syndrome with prominent psychiatric and related behavioral symptoms in the absence of prominent cognitive symptoms, which may also be a dementia prodrome. Objective To compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
132
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(143 citation statements)
references
References 37 publications
7
132
0
4
Order By: Relevance
“…Some studies suggested that the frequency of symptoms is highly correlated with an increase in benzodiazepine prescriptions during the years preceding a diagnosis of dementia 12, 25, 26. Therefore, the observed association between benzodiazepine use and dementia may be due to confounding by indication and reverse causation.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that the frequency of symptoms is highly correlated with an increase in benzodiazepine prescriptions during the years preceding a diagnosis of dementia 12, 25, 26. Therefore, the observed association between benzodiazepine use and dementia may be due to confounding by indication and reverse causation.…”
Section: Discussionmentioning
confidence: 99%
“…The 2011 National Institute on Aging-Alzheimer’s Association (NIA-AA) consensus recommendations for diagnosis of all cause dementia include “changes in personality, behavior, or comportment— symptoms include: uncharacteristic mood fluctuations such as agitation, impaired motivation, initiative, apathy, loss of drive, social withdrawal, decreased interest in previous activities, loss of empathy, compulsive or obsessive behaviors, socially unacceptable behaviors”[26]. While behavioral symptoms are well-recognized early manifestations of Frontotemporal Dementia (FTD) [27], they have been shown to appear early in Alzheimer’s and vascular dementias [28, 29]. It is not uncommon for patients with NPS who do not show obvious cognitive impairment to receive psychiatric diagnoses when the possibility of neurodegenerative disease has been overlooked [30].…”
Section: Introductionmentioning
confidence: 99%
“…Mild behavioral impairment (MBI) is defined as behavioral change lasting six months or longer, in the absence of cognitive and functional impairment (excluding a diagnosis of dementia or MCI or a psychiatric diagnosis) [27]. One prospective outpatient cohort study found that MBI, in the absence of cognitive impairment or a psychiatric diagnosis, was associated with significant risk of dementia (68% to frontotemporal dementia) [27].…”
Section: Introductionmentioning
confidence: 99%
“…One prospective outpatient cohort study found that MBI, in the absence of cognitive impairment or a psychiatric diagnosis, was associated with significant risk of dementia (68% to frontotemporal dementia) [27]. This study described the rates of specific NPS in the sample, but did not address the issue of which specific NPS or patterns of NPS are associated with cognitive decline and comprise the diagnosis of MBI.…”
Section: Introductionmentioning
confidence: 99%